Pengembangan Perangkat Pembelajaran Berbasis TPACK dalam Meningkatkan Aktivitas Belajar dan Kemampuan Pemecahan Masalah Siswa - Bagas Kurnianto; Ridha Sarwono (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2023)
Planning a mature learning device is an important component in determining the direction of Learning objectives. The purpose of this study is to develop TPACK-based learning devices consisting of Learning Implementation Plans, Teaching content, and Assessment Sheets that are valid and effective and to test the effectiveness of TPACK-based learning devices to improve Learning Activities and students' problem solving abilities. The type of research used is Research and Development (ADDIE model). The extensive trial was carried out at Susukan 01 Elementary School, while the implementation of the TPACK learning device product on students' problem solving abilities was carried out at Bakaran Kulon 03 Elementary School. The data collection method consisted of the results of validation of the TPACK learning device, observation, and questionnaires. The results of the research on the broad trial showed that the learning activities at the first meeting to the fifth meeting were included in the